2019
DOI: 10.3390/joitmc5030063
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Conceptual Innovation Model to Reduce Challenges Faced by the Small and Medium Sized Enterprises’ (SMEs) in Bangladesh

Abstract: Small- and medium-sized enterprises (SMEs) in Bangladesh have been growing for the preceding two decades in various ways. Even though these enterprises exert an important effect on the national economy of the country, they face certain challenges and suffer in quite a manner. To reduce the suffering and help deal with these unavoidable challenges, SME foundations in Bangladesh have been working a lot to assist these enterprises. Usually, the challenges are financial, regulatory, or innovation performance-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Research results that support this study include (1) the results of the study by Pech and Vrchota [31], which confirmed that SMEs' economic enterprises have a greater opportunity if they use technology, are easily accessible, and invest in Industry 4.0, thus encouraging increased profits for SMEs; (2) research conducted by Andalib and Halim [32], which emphasized that the challenges faced by SMEs are related to financial performance, regulation, and innovation so that efforts to increase the productivity of SMEs are needed by building innovation and creativity; and (3) research conducted by Nigri and Baldo [33], which emphasized that the effectiveness and efficiency of financial and human resource management will have an impact on economic performance and the sustainability of SME businesses. The three results of these studies are at an intersection with the affirmation that SMEs' economic enterprises that utilize technology, innovation, effectiveness, and efficiency of financial management will have an impact on increasing the profitability and business sustainability of SMEs.…”
Section: Introductionsupporting
confidence: 70%
“…Research results that support this study include (1) the results of the study by Pech and Vrchota [31], which confirmed that SMEs' economic enterprises have a greater opportunity if they use technology, are easily accessible, and invest in Industry 4.0, thus encouraging increased profits for SMEs; (2) research conducted by Andalib and Halim [32], which emphasized that the challenges faced by SMEs are related to financial performance, regulation, and innovation so that efforts to increase the productivity of SMEs are needed by building innovation and creativity; and (3) research conducted by Nigri and Baldo [33], which emphasized that the effectiveness and efficiency of financial and human resource management will have an impact on economic performance and the sustainability of SME businesses. The three results of these studies are at an intersection with the affirmation that SMEs' economic enterprises that utilize technology, innovation, effectiveness, and efficiency of financial management will have an impact on increasing the profitability and business sustainability of SMEs.…”
Section: Introductionsupporting
confidence: 70%
“…The first challenge for craft SMEs is increased production costs. As a result, SMEs will face financial instability and lower profits [24]. Craft SMEs have difficulty searching bank loans because of their low small economies of scale and profitability [25].…”
Section: The Challenge Of Craft Smesmentioning
confidence: 99%
“…A. Rahman, Ahmad, & Taghizadeh, 2019). But unfortunately, the truth is, SMEs' contribution to Bangladeshi GDP is fluctuating because of inconsistent and inadequate performance of SME (Andalib & Halim, 2019;A. Hoque & Awang, 2016;Salam & Hoque, 2019).…”
Section: Introductionmentioning
confidence: 99%